Improving the quality and accuracy of non-invasive blood pressure measurement by visual inspection and automated signal processing of the Korotkoff sounds. (3rd May 2017) - Celler, Branko G; Le, Phu; Basilakis, Jim; Ambikairajah, Eliathamby
Abstract: Objective: In this study we investigate inter-operator differences in determining systolic and diastolic pressure from auscultatory sound recordings of Korotkoff sounds. We introduce a new method to record and convert Korotkoff sounds to a high fidelity sound file which can be replayed under optimal conditions by multiple operators, for the independent determination of systolic and diastolic pressure points. Approach: We have developed a digitised data base of 643 NIBP records from 216 subjects. The Korotkoff signals of 310 good quality records were digitised and the Korotkoff sounds converted to high fidelity audio files. A randomly selected subset of 90 of these data files, were used by an expert panel to independently detect systolic and diastolic points. We then developed a semi-automated method of visualising processed Korotkoff sounds, supported by simple algorithms to detect systolic and diastolic pressure points that provided new insights on the reasons for large differences recorded by the expert panel. Main Results: Detailed analysis of the 90 randomly selected records revealed that peak root mean square (RMS) energy of the Korotkoff sounds, ranged from 3.3 to 84 mV rms, with the lower bound below the audible range of 4–6 mV rms. The diastolic phase was below the minimum auditory threshold in only 47/90 records. This indicates that for approximately 50% of all records diastole could not be determined from Phase V silence. The maximum relative error recorded for systolic pressure between the two methods, auscultatory and visual/algorithmic, was 30.8 mmHg with a mean error of 8.0 ± 5.4 mmHg. We explore the impact of signal morphology and intensity of the Korotkoff sounds, as well as noise, cardiac arrhythmia and the hearing acuity of the operator, on the accuracy of the measurement. Significance: We conclude that large intra-personal variability in Korotkoff signal morphology and amplitudes, as well as variations in the hearing acuity of the operator, make accurate NIBP measurements using sphygmomanometry difficult and should not be used as the gold standard against which automated NIBP devices are calibrated. We propose an alternative method of visualizing the energy of the Korotkoff sounds and applying simple algorithms to determine systolic and diastolic pressure points, which whilst mimicking classical sphygmomanometry eliminates the problems associated with operator hearing acuity and complex and variable Korotkoff signal morphology.